THE INFLUENCE OF SERVICE QUALITY, FOOD QUALITY AND PERCEIVED VALUE ON CUSTOMER SATISFACTION IN PADANG PAYAKUMBUAH - Aqilah, Khonsa Mumtaz; Aini, Husna N; Nuh, Ahmad; Eddy W, Finantyo (Jurnal USAHA, 2024)
The research titled "The Impact of Service Quality, Food Quality, and Perceived Value on Customer Satisfaction at Padang Payakumbuah" focuses on identifying key factors that influence customer satisfaction in the culinary sector, specifically at the BSD branch of Padang Payakumbuah in Tangerang Selatan. Utilizing online questionnaires distributed to customers who dined there in the last three months, the study aims to uncover significant relationships between service quality, food quality, and perceived value. It is anticipated that higher service and food quality will enhance perceived value, leading to increased customer satisfaction. Ultimately, the findings are intended to provide actionable insights for restaurant management to improve service delivery and food offerings, thereby fostering brand loyalty and maintaining Padang Payakumbuah's reputation in the competitive market for traditional Minangkabau cuisine(Dewi et al., 2023).